Piecewise affine policy-based stochastic-robust hosting capacity evaluation of rooftop photovoltaics considering lifecycle carbon contribution - Liu, Hong; Lu, Shaohan; Li, Junkai; Liang, Zipeng; Tong, Yishen; Li, Huiqiang; Chung, Chi-yung; Xue, Li (International journal of electrical power & energy systems, 2025)
•A lifecycle carbon emission-oriented PV hosting capacity evaluation model is developed.•A solution method for stochastic-robust optimization is proposed by simplex approximation-based affine policy. Renewable output curtailment-based hosting capacity improvement provides more carbon contribution by increasing grid-connected zero-carbon energy. However, it also leads to the growth in carbon emission of unit renewable output due to generation abandonment. To evaluate the maximum low-carbon benefits supported by distribution networks, this paper proposes a rooftop photovoltaics (PVs) hosting capacity optimization model considering lifecycle carbon contribution. Specifically, a two-stage stochastic-robust framework is utilized to depict uncertain external carbon intensity and renewable outputs. The product of multiple decision variables contained in this model brings strong nonlinear characteristics. Therefore, a systematic solution methodology is designed to transform nonlinear stochastic-robust model into mixed-integer second-order cone programming. The product of multiple decision variables in “min–max” operator are solved by leveraging dual transformation, simplex approximation-based piecewise affine policy and McCormick relaxation. Numerical results verify that lifecycle carbon contribution increases more than 20% by renewable output curtailment-based hosting capacity improvement.